Fenomenologi Agama Menuju Penghayatan Agama Yang Dewasa - Pius Pandor (Arete, 2012)
One of research methods to analyze religion is phenomenology. This method begins with the phenomenon that appears in consciousness. Experience of religion from teh perspective of phenomenology means that we get into a discourse about subject’s consciousness in the phenomenon which enable someone to get eidos or the essence of religion. From this point of view, subject could distinguish which one constitutes essence or eidos and which one is mere manifestation. This ability is succeeding subject to understand the religion properly. Subject that understands religion properly usually have an ability to accept and celebrates diversity. Besides, subject will always realize that his existence is always in a relation with others’, so that his existence remains as co-existence. This awareness of co-existence at the end leads subject to grow up in the paradigm of pro-existence. It is so crucial a moment amid several violence that takes place in the name of religion in Indonesia that co-existence must be promoted.